THE WISDOM OF LEARNING FROM HIGHER EDUCATION - Suherman Yani (Politeknik Negeri Sriwijaya, 2009)
In this globalization era, people are tempted to commodity knowledge, especially in higher education level because higher education is closely related to the job market. It means that higher education is often influenced by market requirements and more valued on its promising job prospects for its alumni than other function. As a result, people tend to choose higher education with technological innovations and job market orientations.